Principals' Academic Supervision in Improving Teachers' Professional Competence with a Collaborative Supervision Approach - Tomi Itje; Elisabet Siauw; Jenny P. Moleu; Gledis Arafane (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The fundamental problem of teacher quality is influenced by the principal's lack of coaching, mentoring, evaluation, and follow-up in their supervisory role. The purpose of this study is to analyze the principal's academic supervision approach through a collaborative approach. The research design is mixed methods (qualitative and quantitative), with an experimental mixed-methods approach. The research subjects were principals and teachers. Data were collected through observation, interviews, questionnaires, and focus group discussions. The data analysis used in this study was a Sequential Explanatory Design. Based on the data from the field findings, it shows that academic supervision with a collaborative approach significantly increased teacher professional competence, which is reflected in five aspects: increased teacher knowledge in mastering material and teaching abilities, increased teacher skills in interaction, student involvement, and the use of innovative and creative learning styles, improved teacher attitudes and behavior in creating an effective and conducive learning atmosphere, and facilitating the student learning process, increased teacher understanding of the context of professionalism and the use of technology in learning; and increased teacher abilities in evaluating and developing student assessments. This concludes that a collaborative supervision approach can improve teacher professionalism in learning. The implication of this study is the importance of implementing collaborative supervision as an effective strategy to improve teacher professionalism.